Room‐Temperature Blackbody‐Sensitive Photodetector with Visible‐To‐Long‐Wavelength‐Infrared Photoresponse and Ultrafast Speed Based on a Te/PtSe2 Heterostructure - Zhiyuan Dai; Yu Yu; Haibiao Guan; Ruowen Wang; Tao Ye; Yonghao Bu; Jie Deng; Mengdie Shi; Rui Xin; Tianxin Li; Haibo Shu; Xiaoshuang Chen; et al. (Advanced Electronic Materials)
Abstract Room‐temperature blackbody‐sensitive infrared photodetectors with ultra‐broadband and ultrafast photoresponses are highly desired in numerous scientific and technical fields. However, it is challenging for an infrared photodetector to simultaneously possess all the aforementioned characteristics. In this study, a room‐temperature Te/PtSe2 heterostructure photodetector is established to address this challenge, utilizing the built‐in field of the heterostructure, the crossing conduction and valence bands of PtSe2, the high mobilities of both materials, and a considerable photogain. The device is photoresponsive over the ultrabroad wavelength range (519 nm–10 µm). The peak responsivity and specific detectivity reach 196.8 A W−1, and 4.3 × 109 cm Hz1/2 W−1, respectively, at the wavelength of 3.32 µm. The device also exhibits blackbody sensitivity, with a responsivity of 24.8 A W−1, and a specific detectivity of 7.4 × 108 cm Hz1/2 W−1. The photoresponse is ultrafast, corresponding to a 3 dB bandwidth of 160 kHz. The study provides new possibilities for high‐performance room‐temperature infrared detection.